When the invisible hand goes out of hand : an evaluation of crisis responses - Ong, Audrey Sze Yun (Nanyang Technological University, 2021)
Motivated by the recent COVID-induced global recession, this study seeks to shed light on the effectiveness of macroeconomic policy responses in situations of economic crisis. By constructing a granular database of response policies enacted during the 2007 Global Financial Crisis and the 2020 COVID Crisis, we compared countries’ policy choices across financial and pandemic crises, and empirically assessed for optimal compositions of crisis response packages consisting fiscal, labour, welfare and liquidity policies. Broadly, our findings suggest that governments’ policy preferences differ between normal and crisis conditions, as well as across different crisis types. Furthermore, through a series of Fixed Effects regressions, we showed that fiscal interventions should be prioritised when proportioning resources within overarching crisis response packages. Additionally, within such fiscal interventions, focusing on government expenditure is effective for stimulating economic recovery during financial crises, while tax-related interventions work across both financial and pandemic crises. Sectoral-specific fiscal strategies yielded limited effectiveness. All in all, in responding to economic crisis, policymakers should focus on fiscal interventions while considering the specific nature of the crisis at hand to further judge the suitability of fiscal policy sub-types.